Chronic exertional compartment syndrome of the deep posterior compartment the leg: a rare presentation* - Soares Baumfeld, Daniel; Moraes de Oliveira, Gabriel; Koenigkan Ferreira Silva, Matheus; Marques Mourão, João; Soares Baumfeld, Tiago (Journal of the Foot & Ankle, 2024)
The chronic exertional compartment syndrome predominantly affects young athletes and often requires surgery when conservative treatments fail. The anterior compartment is the most commonly involved, accounting for 72.8% of cases, while isolated involvement of the deep posterior compartment is rare, occurring in only 2.8% of cases. This study presents a case of isolated deep posterior compartment syndrome and demonstrates a minimally invasive decompression technique for faster rehabilitation and early return to activity. A 26-year-old male athlete presented with posterior leg pain after running, unresponsive to conservative treatment. Stress magnetic resonance imaging revealed isolated deep posterior compartment involvement. Patient underwent minimally invasive segmental fasciotomy of the leg’s four compartments, with excellent postoperative recovery and no deficits. Surgical intervention remains the gold standard for maintaining activity levels in athletes, and a high index of suspicion is crucial for diagnosis and treatment of this rare pathology. Level of evidence IV; Therapeutic study; Case report.